Tantangan Diagnostik pada Leukemia Akut: Laporan Kasus tentang Hasil Pemeriksaan Sumsum Tulang yang Tidak Jelas dengan Adanya Sel Blast pada Sediaan Darah Perifer: Laporan Kasus - Dewi, Putu Itta Sandi Lesmana; Dharmayudha, Tjokorda Gede (Cermin Dunia Kedokteran, 2026)
Introduction: Acute leukemia is a hematologic malignancy characterized by the proliferation of immature leukocytes that disrupt normal hematopoiesis, leading to cytopenias and systemic symptoms. Diagnosis typically relies on bone marrow evaluation. Peripheral blood findings may be critical when marrow results are inconclusive. Case: A 23-year-old male with melena, severe anemia, generalized weakness, and a two-week history of back pain. Physical examination revealed pallor and splenomegaly. Initial laboratory findings showed severe macrocytic anemia, leukocytosis, and thrombocytopenia. A peripheral blood smear revealed 63% blasts with a high nuclear-to-cytoplasmic ratio and prominent nucleoli. Despite these findings, the diagnosis of acute leukemia, bone marrow aspiration was inconclusive. Elevated lactate dehydrogenase indicated a high tumor burden. Discussion: Peripheral smear evaluation, supported by cytogenetic and flow cytometry studies, is vital for early diagnosis. Acute leukemia must remain a differential consideration even in the absence of definitive bone marrow findings. Conclusion: This case highlights the diagnostic challenge of acute leukemia with inconclusive initial bone marrow findings. Peripheral blood smear detection of circulating blasts was crucial in establishing the diagnosis. Early recognition through integrated diagnostic evaluation remains essential for the timely initiation of treatment.